Optimization of line pattern transfer of integrated optical mach-zender interferometer for optical sensor
Conventional photolithography usually used in in-house fabrication process to transfer the design of line pattern. This research lays the foundation for the optimization of photo lithography process for line pattern transfer of complex optical circuitry. Integrated Optical Mach-Zehnder Interferometer (IO-MZI) has been widely used for biosensor applications. In order to have a significant advantage in improving the sensitivity of the biosensor, it is crucial to get a good, consistent and conformal line pattern transfer with a fine width; in our case is approximately 4μm and 3cm length. However, the success rate of 10-MZI pattern transfer had been low using the conventional multi-development process. One of the main factors is the particle contamination due to the usage of reused developer bath. In this work, an innovative single development process had been proposed with the utilization of the same conventional set-up. The concept of this method centers around the optimization of the total development time based on the experimental and mathematical model of the development rate. By doing so, the development process can be completed with only one immersion of the substrate in the developer bath. Due to this reason, the aim of this project is to improve the success rate and repeatability of photolithography process without compromising the resolution and vertical profile, which is necessary for the optical waveguide fabrication. Besides, the manipulation of development rate by varying exposure time in this work also revealed the possibility of manipulation of linewidth based on the exposure time. In short, the proposed single development process had increased the success rate of 10-MZI pattern transfer from 300/o (multi-development method) to 90% (single-development method). The characterization of in-house single development fabrication process has improved the current photolithography setup for line pattern transfer and complex design pattern transfer.